HeartMate 3 pump exchange via sternal‐sparing bilateral minithoracotomies. Issue 4 (25th February 2020) - Louis, Clauden; Ayers, Brian; Barrus, Bryan; Prasad, Sunil; Alexis, Jeffrey D.; Bernstein, Wendy; Cheyne, Christina; Gosev, Igor
Abstract: As median survival for left ventricular assist device (LVAD) patients increases, the incidence of adverse events requiring device exchange is likely to increase as well. Less invasive surgical approaches for device exchange of older generation pumps have demonstrated multiple potential benefits compared with median sternotomy. However, there remains a paucity of data in regard to less invasive surgical techniques for the exchange of the newest generation intrapericardial devices. In this report we describe a complete sternal‐sparing technique for the LVAD exchange of a HeartMate 3 via bilateral minithoracotomies.